Effect of weather conditions on leans of one Eugenia Grandis tree in Singapore - Li, Yangyang (2021)
An approach to model the effect of weather conditions on tree stability is presented, where the weather conditions include wind, rainfall, temperature, humidity and solar radiation. The weather conditions could affect the rainwater infiltration and evapotranspiration, hence change the water content in the soil and influence the soil properties such as stiffness and strength when resisting the wind drags on the tree. One-dimensional (1D) modelling in GeoStudio 2012 was used to analyse the pore-water pressure head distribution in soil under the recorded weather conditions for 20 days. Three-dimensional (3D) modelling in ANSYS 19.1 was then used to analyse the leans of one Eugenia Grandis tree deformed by wind drags in Singapore during the 20 days. The soil modulus and soil strength were considered as functions of the water content in the soil, which were computed from VADOSE modelling in GeoStudio 2012 under the real time weather conditions measured from the field instrumentations. Moreover, the wind drags were calculated from a previous study that analysed the drag coefficient on the same Eugenia Grandis tree. The leans of the Eugenia Grandis tree under wind drags during the studied period were computed by incorporating the change in soil stiffness and soil strength due to the change in water content of the soil. The computed tree leans from the analyses increased by 16.5% when the soil strength and soil modulus changed with water content of the soil as compared to the computed tree leans without the incorporation of the changes in soil strength as an effect of weather conditions and assuming a constant soil modulus of 20 MPa. It is suggested that effect of weather conditions on soil should be considered in the analyses related to tree deformations.